APLIKASI IRIGASI TETES BERTINGKAT PADA TANAMAN SEMUSIM MENDUKUNG KETAHANAN PANGAN KELUARGA DI LINGKUNGAN PERMUKIMAN KOTA MATARAM - NEGARA, I DEWA GEDE JAYA; SUPRIYADI, ANID; PRACOYO, ATAS; YASA, I WAYAN (GANEC SWARA, 2024)
The use of multistage drip irrigation needs to be supported by adequate planting media so that irrigation water can be provided optimally. The planting medium used is practically soil mixed with compost and put in a polybag. Therefore, by adding compost with a certain composition to the soil, it is hoped that a good planting medium will be obtained. This test aims to determine the effect of using cocopeat compost and cow compost as well as soil as a planting medium in polybags on providing multistage drip irrigation. Flow characteristics on the distribution of irrigation water, its absorption capacity, absorption rate and irrigation uniformity achieved. The test was carried out on a ½” PVC drip irrigation network with a 2 lt/hour emitter consisting of 4 network levels on land measuring 2m x 4m, water source from a tower with a height of around 2.5m and a tank capacity of 150 liters. Test data for analysis consists of irrigation volume and distribution, drip system flow rate, irrigation uniformity (Cu), infiltration rate and irrigation depth. The analysis results show that the average irrigation distribution on floors 1 to 4 is 3028ml, 2937ml, 2848.25ml and 2793 ml, with flow rates on floors 1 to 4 of 40ml/s, 39 ml/s, 38 ml/s and 37 ml/sec. The amount of drip discharge (qt) on the 1st floor was 6.7ml/sec, on the 2nd floor the amount was 6.5 ml/sec, on the third floor it was 6.3 ml/sec and 6.2ml/sec on the 4th floor. Irrigation uniformity was obtained by 96% is considered very good, with an average infiltration rate hc in V2 of 0.04 cm/s, in V3 the hc was 0.03cm/s and in V4 the hc was 0.027cm/s. So the irrigation infiltration rate when using cocopeat tends to decrease if the portion of the planting medium increases, so its use needs to be limited.